Pengaruh Leverage dan Likuiditas terhadap Financial Distress dengan Profitabilitas sebagai Pemoderasi - Maulidya, Putri; Rida Prihatni; Indah Muliasari (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
This study aims to determine the effect of leverage and liquidity on financial distress with profitability as a moderation. The population of this study is consumer cyclicals companies listed on IDX during the 2019-2021 period. The sampling method used purposive sampling. The analysis techniques used descriptive statistics, multicollinearity tests, logistic regression, and moderated regression analysis. The results show that leverage has a significant positive effect on financial distress, while liquidity has no effect on financial distress. In addition, profitability is able to moderate the effect of liquidity on financial distress, but unable to moderate the effect of leverage on financial distress.